2013
DOI: 10.1186/1475-2840-12-110
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade albuminuria is associated with early but not late carotid atherosclerotic lesions in community-based patients with type 2 diabetes

Abstract: BackgroundLow-grade albuminuria is associated with cardiovascular risk factors and mortality. Our aim was to investigate the association between low-grade albuminuria and carotid atherosclerotic lesions in community-based patients with type 2 diabetes.MethodsA cross-sectional study was performed in 475 community-based patients with type 2 diabetes (190 males and 285 females) with normal urinary albumin-to-creatinine ratios (UACR) (< 3.5 mg/mmol) from Shanghai, China. The subjects were stratified into tertiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 55 publications
(56 reference statements)
4
25
1
2
Order By: Relevance
“…However, our study provides novel information that high normal albuminuria is significantly associated with subclinical atherosclerosis independent of the presence of DMR. Moreover, our results showed significant associations between low-grade albuminuria and both early and late carotid atherosclerosis, inconsistent with the findings of Li et al [9]. The discrepancy might be related to the much lower prevalence of carotid stenosis in the study of Li et al (<4%; carotid stenosis defined as any degree of narrowing of the carotid arteries by carotid plaque) compared to that in the present study (19.6%; carotid stenosis defined as 50% or greater of luminal narrowing), raising the possibility of an underpowered calculation in Li et al…”
Section: Comparison With Previous Reportscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our study provides novel information that high normal albuminuria is significantly associated with subclinical atherosclerosis independent of the presence of DMR. Moreover, our results showed significant associations between low-grade albuminuria and both early and late carotid atherosclerosis, inconsistent with the findings of Li et al [9]. The discrepancy might be related to the much lower prevalence of carotid stenosis in the study of Li et al (<4%; carotid stenosis defined as any degree of narrowing of the carotid arteries by carotid plaque) compared to that in the present study (19.6%; carotid stenosis defined as 50% or greater of luminal narrowing), raising the possibility of an underpowered calculation in Li et al…”
Section: Comparison With Previous Reportscontrasting
confidence: 99%
“…With regards to atherosclerotic markers, several crosssectional studies demonstrated that a high ACR within the normal range was independently associated with increased carotid intima-media thickness and/or carotid plaques in various populations [6e8] and patients with T2DM [9,10]. However, previous studies rarely included the presence of DMR, a major confounding variable in the analysis.…”
Section: Comparison With Previous Reportsmentioning
confidence: 99%
“…Both the carotid and lower limb arteries were subjected to Doppler ultrasound examinations that include measurements of IMT, atherosclerotic plaque and stenosis as described in previous studies in detail [ 11 15 ]. The definitions of CIMT, FIMT, carotid and lower limb atherosclerotic plaques and stenosis had also been described in detail in our previous studies [ 11 14 , 16 ]. In the present study, atherosclerotic plaque and stenosis were defined as the presence of either carotid or lower limb arterial atherosclerotic plaques and stenoses, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The physical and laboratory examinations used in the present study have been described previously 13 . The glomerular filtration rate (eGFR) was assessed by the simplified Modification of Diet in Renal Disease formula: 186.3 9 (serum creatinine) -1.154 9 (age) -0.203 (90.742 if female) 14 .…”
Section: Physical Examination and Laboratory Testingmentioning
confidence: 99%